Governance reaction to the emerging megacity shrinkage in Tokyo: The case of the Tsukuba express transit-suburban region. (February 2021) - Tateishi, Eigo; Takahashi, Kyoko; Nakano, Taku
Abstract: This article provides insight into how the governance system of megacities, as an assemblage of many different factors, can preemptively react to emerging shrinkage. This is a topic that is rarely addressed in the current literature. The article examines the suburban region of the Tokyo Megacity served by the Tsukuba Express. The region is studied both quantitatively and qualitatively using a mixed-methods approach, and the results are related to the governance system model as originally developed. The results suggest that shrinkage-preemptive governance involves a mix of pro-growth and shrinkage-adapting strategies, but that implementing such strategies through interpolicy and intermunicipal coordination is problematic in growing metropolitan suburbs. We suggest (1) the national government plays a role in interpolicy coordination and regional governance of shrinkage, (2) the formation of political consciousness around regional transit infrastructure to foster regional coordination, and (3) a regional effort to restructure regional socio-economic identities to mitigate dependence on Tokyo and enhance economic resilience. This study shows that governance system models can assist planners and policymakers in engaging with the complexity of post-growth urban challenges. Highlights: Governance of megacity shrinkage is an emerging topic in the shrinkage literature. A conceptual model of shrinkage governance was made by extensive literature review. Empirical evidence supports the effectiveness of the model with additional insights. Growth and shrinkage proactive actions can coexist despite some policy challenges. Social process in a center-periphery relation makes regional coordination difficult.